Astrotheology: A proactive contextualization of novelty within space exploration - A.C. Pieterse (Acta Theologica)
Space exploration is the dawn of a new era for humanity and the need for theological reflection is essential. Astrotheology, as the vehicle of choice, is predominantly reactive in nature. I intend to challenge this reactive function of theology and propose that theology might be called to play a proactive, even prophetic role especially within the science and religion debate. Scripture’s specific revelation vis-à-vis the essence of the natural world and the nature of God may provide a proactive contextualisation of novelty for future space exploration. Astrotheology underlines certain attributes in nature, embedded within the fabric of space and time, that could magnify and frame our understanding of empirical observations. We live in a universe where there is a space for contingency and novelty; yet a creation that is lawful; there is also a movement towards entropy, and, finally, certain aspects in creation will remain a mystery.